(untitled) (Texas Journal of Medical Science, 2023)
Women of childbearing age are at a higher risk of developing various health issues, including reproductive disorders and chronic diseases such as diabetes and hypertension. Family doctors play a crucial role in the prevention and management of these diseases through regular check-ups, counseling, and early detection. This article aims to explore the role of family doctors in the prevention of diseases of women of childbearing age, with a focus on reproductive health, chronic disease management, and health promotion. The study is based on a literature review of relevant articles published in peer-reviewed journals. The findings highlight the importance of regular check-ups, health education, and early detection in preventing and managing diseases in this population.